Duopolistic competition with multiple scenarios and different attitudes toward uncertainty. (1st November 2017) - Monroy, L.; Caraballo, M.A.; Mármol, A.M.
Abstract: In this paper, we address duopolistic competition when the firms have to assess the results of the interaction at different scenarios. Specifically, we consider the case in which the scenarios are identified with several states of nature and, therefore, the firms face uncertainty on their results. The probability of occurrence of the scenarios is unknown by the firms and they make their output decision before uncertainty is resolved. Within this framework, we analyze competition between firms when these firms exhibit extreme and neutral attitudes toward uncertainty with respect to the final profits. For the variety of cases that can occur, we characterize the sets of equilibria, and provide procedures to determine them. The analysis proposed can also be applied to study situations in a deterministic setting with simultaneous multiple scenarios, and to the analysis of multiple criteria duopolistic competition.